2020
DOI: 10.1016/j.tree.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture and the Disruption of Plant–Microbial Symbiosis

Abstract: Domestication has transformed hundreds of wild plant species into productive cultivars for human utility. However, cultivation practices and intense artificial selection for yield may entail a hidden cost: the disruption of interactions between plants and beneficial microbiota. Here, we synthesize theory predicting that evolutionary trade-offs, genetic costs, and relaxed selection disrupt plant-microbial symbiosis under domestication, and review the wealth of new data interrogating these predictions in crops. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 123 publications
2
113
0
1
Order By: Relevance
“…Comparisons between crops and their wild relatives have indicated that domestication has altered their interactions with microorganisms (Peŕez-Jaramillo et al, 2018), sometimes resulting in plants that form symbioses with resource mutualists, such as arbuscular mycorrhizal fungi, less readily (Martıń-Robles et al, 2018). Breeding under high-input agricultural regimes (e.g., ample fertilizer) may make roots less conducive to forming microbial symbioses and relax selection on the ability to form symbioses-or even select against forming symbioses due to the costs of maintaining them when resources are abundant (Peŕez-Jaramillo et al, 2016;Porter and Sachs, 2020). Furthermore, breeding crops for improved pathogen resistance may also inadvertently reduce the ability of plants to form symbioses with mutualistic microbes due to common pathways of colonization (Porter and Sachs, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons between crops and their wild relatives have indicated that domestication has altered their interactions with microorganisms (Peŕez-Jaramillo et al, 2018), sometimes resulting in plants that form symbioses with resource mutualists, such as arbuscular mycorrhizal fungi, less readily (Martıń-Robles et al, 2018). Breeding under high-input agricultural regimes (e.g., ample fertilizer) may make roots less conducive to forming microbial symbioses and relax selection on the ability to form symbioses-or even select against forming symbioses due to the costs of maintaining them when resources are abundant (Peŕez-Jaramillo et al, 2016;Porter and Sachs, 2020). Furthermore, breeding crops for improved pathogen resistance may also inadvertently reduce the ability of plants to form symbioses with mutualistic microbes due to common pathways of colonization (Porter and Sachs, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…, ample fertilizer) may make roots less conducive to forming microbial symbioses and relax selection on the ability to form symbioses—or even select against forming symbioses due to the costs of maintaining them when resources are abundant ( Pérez-Jaramillo et al., 2016 ; Porter and Sachs, 2020 ). Furthermore, breeding crops for improved pathogen resistance may also inadvertently reduce the ability of plants to form symbioses with mutualistic microbes due to common pathways of colonization ( Porter and Sachs, 2020 ). Wild sunflower accessions are slightly more readily colonized by mycorrhizae ( Turrini et al., 2016 ) and also less resistant to pathogens than domesticated lines ( Leff et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was hypothesized that natural hosts (wild species) might have evolved signaling mechanisms to preferentially partner with more mutualistic symbionts and to disadvantage less-cooperative ones ( Younginger and Friesen, 2019 ). Evolutionary models predict that such natural surveillance capability can be disrupted during domestication bottlenecks or breeding process because of: (i) trading-offs between partner quality and agricultural traits as a result of negative trait association or antagonistic gene pleiotropy, such as defense versus symbiosis ( Chen et al, 2017 ; Wood et al, 2018 ) or (ii) relaxed selection against symbiosis disruption in nitrogen-rich soils owing to a lack of observable fitness costs over disrupted symbiosis ( Porter and Sachs, 2020 ). For example, when plants are grown in high-input agricultural soils, genotypes with reduced symbiosis capability are likely to have higher yields because they can freely get sufficient nitrogen from soil without need to allocate photosynthates to rhizobia for symbiosis development.…”
Section: Effect Of Domestication and Breeding On Partner Choice And Smentioning
confidence: 99%
“…It has been predicted that this dramatic transition from the wild to cultivation might have resulted in selection of genotypes that are more reliant on soil nitrogen and thus less able to take advantage of symbiotic nitrogen fixation, even though the symbiosis property is universally retained ( Werner et al, 2015 ; Turcotte et al, 2017 ; Porter and Sachs, 2020 ). Such genetic shifts can be the consequence of relaxed selection on symbiosis traits, leading to altered host-bacteria compatibility, genotype-dependent root and soil microbial community, and the host’s ability to discriminate between high-efficient and low-efficient bacterial partners ( Kiers et al, 2003 , 2007 ; Westhoek et al, 2017 ; Porter and Sachs, 2020 ). Here, we review how domestication, breeding and agricultural practices might have affected the symbiosis traits in legumes and also provide a perspective on how such knowledge can be used for development of strategies to improve symbiotic nitrogen fixation in sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%